Function Of Reading Fictions In Language Development - Abdigapbarova, Zhanar (Journal of Foreign Language Teaching and Applied Linguistics, 2019)
In current time, it can be noticed that literature plays such a small role in the life of modern society. The new generation departs from the literary and educational tradition, which was very strong, developing over several centuries. The reading circle has changed significantly under the influence of the demand for special literature and books containing all sorts of practical advice, and not on those that educate a person morally. Reading literature serves as a reflection of reality, a product of art, and acknowledgment with nations’ culture. It occupies a special place in the philosophy of language learning, enriching vocabulary, improving aesthetic taste and humor. Each nation can collect its historical memory and historical consciousness through literature with hundreds of fictions, describing the traditional culture of ancestors. Additionally, the reading of fiction has a beneficial effect on the mind, developing and improving its quality. It plays an important role to understand the richness of the language and to expand the vocabulary in the language learning process. The reading of fictions arouse people’s keen interest in the culture of other nations, the understanding of their worldviews. In any language, there are polysemy of words, synonyms, antonyms, homonyms, etc. For perfect mastery of the language, it is necessary to understand the expression of words. In fictions, the word is used in various meanings. Therefore, when learning a language, it is very useful to work with literary texts. Today, the student has his /her own peculiarities in the choice of text, that is, in the choice of fictions. In this article, based on experience of teaching literature, the effectiveness of the use of fictions in language learning and the methods of its use will be considered, as well as the effective aspects of the development of a language through fiction will be analyzed.
Keywords: fiction; language development; literature; culture.